Seroprevalence of hepatitis B and C virus among a group of hemophilia patients in Kurdistan Region, Iraq - Salih A. Hama (Journal of Clinical Virology Plus)
Background: The risk of blood-borne infections, particularly hepatitis B virus (HBV) and hepatitis C virus (HCV), continues to persist in developing countries among patients who receive blood products, such as hemophiliacs, but there is a lack of up-to-date data in such countries. This study aims to determine the prevalence of HBV and HCV infections among a group of hemophilia patients in Kurdistan Region, Iraq. Methods: This prospective cross-sectional study, conducted from June to September 2022, screened 117 hemophilic patients in the region for Hepatitis B surface antigen (HBsAg) and anti-HCV antibodies using serologic assays. Results: One hundred fifteen participants were male (98.3 %) with a mean age of 20.7 years (8–47). HBV seropositivity was found in 9 (7.7 %) patients, while HCV seropositivity was noted in 15 (12.8 %). No significant correlation was observed between HBV/HCV infectivity status and age, residency, or education status (p < 0.05). The prevalence of only HBV was significantly higher among patients with more frequent clotting factor intake (p = 0.016), which was associated with lower odds of HBV positivity (OR = 0.034, 95 % CI: 0.002–0.492). Moreover, HCV seropositive patients were more commonly associated with surgical history compared to negative cases (20 %vs. 3.9 %; p = 0.044), which was associated with significantly increased odds of HCV positivity (OR = 6.125, 95 % CI: 1.221–30.719). Conclusion: This study reveals an intermediate prevalence of HBV (7.7 %) and a high prevalence of HCV (12.8 %) infections among hemophilia patients in the Kurdistan Region, Iraq.